Hypoglycemic and antioxidant activities of Jasminum officinale L. with identification and characterization of phytocompounds - Thakur, Mehak; Verma, Rachna; Kumar, Dinesh; Manickam, Sivakumar; Ullah, Riaz; Ibrahim, Mohamed A; Bari, Ahmed; Lalhenmawia, H; Kumar, Deepak (Heliyon, 2024)
The utilization of plant-derived chemicals with anti-diabetic properties is widely promoted for its advantageous tactics in managing diabetes, as they are cost-effective and have minimal or no adverse effects. Therefore, this work investigates the medicinal plant Jasminum officinale L. leaves by extraction and bio-guided fractionation. The ethyl acetate fraction showed a higher yield of 36.4 %. A phytochemical test on Jasminum officinale confirmed flavonoids, saponins, phenols, and tannins. The highest total phenol and flavonoid contents in the ethyl acetate fraction of J. officinale are 103.01 ± 1.1 mg GAE/g and 80.29 ± 1.03 mg QUE/ value found in methanol crude extract. Furthermore, HPTLC analysis of the ethyl acetate fraction detected the existence of flavonoids (kaempferol) and phenols (gallic acid, quercetin, and rutin). The compounds detected at the greatest concentrations in the LC-M/MS analysis of the ethyl acetate fraction were cirsiliol, kaempferol, and 2-tridecanone. Additionally, J. officinale (IC50 33.845 ± 1.09 μg/mL) demonstrated the highest DPPH scavenging activity in EAF like that of ascorbic acid (IC50 22.27 ± 0.96 μg/mL). Also, in the FRAP assay, the IC50 of this fraction is 15.14 ± 0.25 μM Fe equivalents. In the range of alpha-amylase deactivating action, from 13.25 % to 74.51 %, and IC50 value (47.40 ± 0.29 μg/mL) was significantly higher in the ethyl acetate fraction of J. officinale leaf extract. Moreover, J. officinale leaf extract had a substantially higher retention of glucose level (23.92 ± 0.85 % to 87.21 ± 0.6 %), significantly higher anti-inflammatory activity with the lowest IC50 value (66.00 ± 1.84), and lipid peroxidation (IC50 value 34.67 ± 1.69) by utilizing egg yolk as a substrate for lipids. Overall, the study revealed that J. officinale has considerable anti-diabetic characteristics. However, further comprehensive research is necessary to ascertain the medicinal purposes of J. officinale and its chemical components, pharmacological effects, and clinical uses.
Keywords: Anti-inflammatory; Phytochemicals; Glucose uptake; Diabetes; Jasminum officinale; Antioxidant